2024
DOI: 10.3390/jcm13051499
|View full text |Cite
|
Sign up to set email alerts
|

The Management of a Geriatric Patient Using Dabigatran Therapy on Dentigerous Cyst with Oral Bleeding

Glauco Chisci,
Dafne Chisci,
Enea Chisci
et al.

Abstract: Jaw cysts represent a great matter of interest in oral and maxillofacial surgery. Jaw cyst surgery is a common intervention in oral surgery but, in the case of a multidisciplinary patient, the oral surgeon needs to meet with other specialists. A cyst is an epithelium-lined sac containing fluid and/or semisolid material due to epithelial cell proliferation, degeneration, and liquefaction; the hypertonic solution withdraws liquids from the surrounding tissues, while internal pressure exerts an equal strength on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…With regards to the management of postoperative hemorrhagic complications, some authors used selective transarterial embolization in order to treat the emergence after third molar extraction or to enhance coagulation after venous mandibular neoformation surgery [ 26 , 27 , 28 , 29 ]. Gogulanathan et al [ 30 ] in their interesting randomized slit-mouth clinical trial reported superior results after third molar extraction in the group with fibrin sealant compared to traditional suture, with superior values of postoperative wound closure and mouth opening and reduced values in duration to achieve hemostasis and pain score.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the management of postoperative hemorrhagic complications, some authors used selective transarterial embolization in order to treat the emergence after third molar extraction or to enhance coagulation after venous mandibular neoformation surgery [ 26 , 27 , 28 , 29 ]. Gogulanathan et al [ 30 ] in their interesting randomized slit-mouth clinical trial reported superior results after third molar extraction in the group with fibrin sealant compared to traditional suture, with superior values of postoperative wound closure and mouth opening and reduced values in duration to achieve hemostasis and pain score.…”
Section: Discussionmentioning
confidence: 99%